Kinetic simulation of electron cyclotron resonance assisted gas breakdown in split-biased waveguides for ITER collective Thomson scattering diagnostic - Trieschmann, Jan; Larsen, Axel Wright; Mussenbrock, Thomas; Korsholm, Søren Bang (Physics of Plasmas, 2021)
For the measurement of the dynamics of fusion-born alpha particles Ea 3:5 MeV in ITER using collective Thomson scattering (CTS), safe transmission of a gyrotron beam at mm-wavelength (1 MW, 60 GHz) passing the electron cyclotron resonance (ECR) in the in-vessel tokamak “port plug” vacuum is a prerequisite. Depending on neutral gas pressure and composition, ECR-assisted gas breakdown may occur at the location of the resonance, which must be mitigated for diagnostic performance and safety reasons. The concept of a split electrically biased waveguide (SBWG) has been previously demonstrated in C.P. Moeller, U.S. patent 4,687,616 (1987). The waveguide is longitudinally split and a kV bias voltage is applied between the two halves. Electrons are rapidly removed from the central region of high radio frequency electric ﬁeld strength, mitigating breakdown. As a full scale experimental investigation of gas and electromagnetic ﬁeld conditions inside the ITER equatorial port plugs is currently unattainable, a corresponding Monte Carlo simulation study is presented. Validity of the Monte Carlo electron model is demonstrated with a prediction of ECR breakdown and the mitigation pressure limits for the above-quoted reference case with 1H2 (and pollutant high Z elements). For the proposed ITER CTS design with a 88.9 mm inner diameter SBWG, ECR breakdown is predicted to occur down to a pure 1H2 pressure of 0.3 Pa, while mitigation is shown to be effective at least up to 10 Pa using a bias voltage of 1 kV. The analysis is complemented by results for relevant electric/magnetic ﬁeld arrangements and limitations of the SBWG mitigation concept are addressed.